2017
DOI: 10.1002/jbio.201600217
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low level laser therapy on both HIV‐1 infected and uninfected TZM‐bl cells

Abstract: Human immunodeficiency virus (HIV-1) infection remains a major health problem despite the use of highly active antiretroviral therapy (HAART), which has greatly reduced mortality rates. Due to the unavailability of an effective vaccine and treatment that would completely eradicate the virus in infected individuals, the quest for new therapies continues. Low level laser therapy (LLLT) involves the exposure of cells to low levels of red or infrared light. LLLT has been widely used in different medical conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The notably high levels of luciferase activity as shown by RLUs in the presence of HIV was a clear indication that TZM-bl cells are permissive to HIV infection and the ZM53 virus used was infectious. An observation similar to the one made in a previous [ 45 ], showed that irradiation caused reduction in HIV infection as seen in [ Fig. 6 ].…”
Section: Discussionsupporting
confidence: 89%
“…The notably high levels of luciferase activity as shown by RLUs in the presence of HIV was a clear indication that TZM-bl cells are permissive to HIV infection and the ZM53 virus used was infectious. An observation similar to the one made in a previous [ 45 ], showed that irradiation caused reduction in HIV infection as seen in [ Fig. 6 ].…”
Section: Discussionsupporting
confidence: 89%
“…Further, we analysed the cytotoxic impact of our single LLLT dose on SVF cells showing no difference between untreated cells and cells undergoing LLLT. Lugongolo, Manoto, Ombinda‐Lemboumba, Maaza, & Mthunzi‐Kufa, made an interesting observation after application of laser irradiation to infected (HIV‐1) and uninfected cells, demonstrating no inhibitory effect on uninfected cells but induced cell damage in the HIV‐1 infected cells in a dose‐dependent manner (Lugongolo et al, ). Another study was performed using the effect of photobiomodulation on endothelial cells where the LDH release was decreased and the viability increased after red and near‐infrared laser treatment (Franco et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…3.4 J/cm 2 M13 bacteriophage, Murine cytomegalovirus Log (pfu): 5 for M13 bacteriophage at 1 h of laser exposure time [ 31 ] Blue Femtosecond laser (400 nm). 20 mJ/pulse M13 bacteriophages Log 10 (Loud reduction): 5.8 ± 0.3 and 2.9 ± 0.15 at 15 and 2 min, respectively [ 32 ] Blue laser (408 nm), Low-power ultrashort pulse (USP), 150 mW Murine Norovirus > 3 log10 inactivation at 3 h [ 33 ] Red Laser, LLLT (660 nm), 2–10 J/cm 2 , 626 s HIV-1 Luciferase activity: Reduction in infected cells (8 J/cm 2 ) and no inhibitory effect in uninfected cells [ 34 ] Infrared Femtosecond laser (800 nm), 4 μW, 10 ms HIV-1 Luciferase activity: Two-fold reduction with Radiation and Raltegravir for 30 min [ 35 ] …”
Section: Introductionmentioning
confidence: 99%